Social/Communication Skills, Cognition, and Vocational Functioning in Schizophrenia - Dickinson, Dwight (Oxford University Press, 2007)
Deficits in social/communications skills have been documented in schizophrenia, but it is unclear how these deficits relate to cognitive deficits and to everyday functioning. In the current study, social/communication skills performance was measured in 29 schizophrenia patients with a history of good vocational functioning (GVF) and 26 with a history of poor vocational functioning (PVF) using a role-play–based social skills assessment, the Maryland Assessment of Social Competence (MASC). A battery of standard cognitive tasks was also administered. MASC-indexed social skills were significantly impaired in PVF relative to GVF patients (odds ratio = 3.61, P < .001). Although MASC social skills performance was significantly associated with cognitive performance in domains of verbal ability, processing speed, and memory, the MASC nevertheless remained an independent predictor of vocational functioning even after controlling for cognitive performance. Social/communications skills predict vocational functioning history independently of cognitive performance, and social skills measures should be considered for inclusion in test batteries designed to predict everyday functioning in schizophrenia.